The Phenomenon of Lifelong Singles in Indonesia: An Islamic Law and Psychological Health Study - Hadi , Bagus Kusumo; A’dawiyah , Robi’atin; Zaelani , Abdul Qodir; Na'im, Arroyan; Azizah, Asyifa Nur (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The phenomenon of singlehood or remaining unmarried often sparks debates within society, addressing aspects of religion, psychology, and health. The decision not to marry is often viewed as deviating from social norms and generates negative stigma, leading to various issues related to acceptance and its impact on individuals. This study employs a descriptive qualitative method to examine this phenomenon from multiple perspectives. Islamic law provides flexibility for individuals to remain unmarried, as long as the decision is based on the intention of piety and worship. Prominent scholars such as Imam Shafi'i and Imam Nawawi assert that living without a spouse is permissible, as long as it remains oriented towards spiritual goals. From a psychological standpoint, the choice to remain unmarried is influenced by factors such as family dynamics, views on independence, and life experiences. This decision may offer benefits, such as career development and personal freedom, but it can also present challenges in the form of social pressure and the risk of loneliness. From a health perspective, marital status is closely linked to both physical and mental well-being. Unmarried individuals tend to face a higher risk of mental health issues, such as depression and anxiety, yet they are also spared from marital conflicts that may negatively affect psychological well-being. This study concludes that the choice of singlehood can be understood from various viewpoints, while considering the individual’s circumstances, intentions, and needs. The contribution of this research is to provide a multidimensional insight into singlehood, which can serve as a reference for policymakers, health practitioners, and society in supporting individuals who choose this path wisely and with respect.